2014
DOI: 10.1080/13546783.2014.918562
|View full text |Cite
|
Sign up to set email alerts
|

A randomised Monty Hall experiment: The positive effect of conditional frequency feedback

Abstract: The Monty Hall dilemma (MHD) is a notorious probability problem with a counterintuitive solution. There is a strong tendency to stay with the initial choice, despite the fact that switching doubles the probability of winning. The current randomised experiment investigates whether feedback in a series of trials improves behavioural performance on the MHD and increases the level of understanding of the problem. Feedback was either conditional or non-conditional, and was given either in frequency format or in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
(69 reference statements)
0
20
1
Order By: Relevance
“…In addition, in the study of Herbranson and Wang (2014) and in one experimental condition (with the classical MHD) of the study of Mazur and Kalhbaugh (2012), participants showed no significant increase in switching rates over trials. These participants, however, already showed a high switching rate in the first block of trials as compared to other studies (Franco-Watkins et al, 2003; Klein et al, 2013; Petrocelli, 2013; Petrocelli & Harris, 2011; Saenen et al, 2015b; Slembeck & Tyran, 2004). An important question that arises with the evidence of increased switching behaviour across successive trials is whether participants gain understanding of the problem as well.…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…In addition, in the study of Herbranson and Wang (2014) and in one experimental condition (with the classical MHD) of the study of Mazur and Kalhbaugh (2012), participants showed no significant increase in switching rates over trials. These participants, however, already showed a high switching rate in the first block of trials as compared to other studies (Franco-Watkins et al, 2003; Klein et al, 2013; Petrocelli, 2013; Petrocelli & Harris, 2011; Saenen et al, 2015b; Slembeck & Tyran, 2004). An important question that arises with the evidence of increased switching behaviour across successive trials is whether participants gain understanding of the problem as well.…”
Section: Resultscontrasting
confidence: 59%
“…The results of most of these studies provide strong evidence for learning from experience: Increased switching rates over trials were observed (Franco-Watkins et al, 2003; Herbranson & Schroeder, 2010; Hirao et al, 2017, Klein et al, 2013; Mazur & Kahlbaugh, 2012; Petrocelli, 2013; Petrocelli & Harris, 2011; Saenen et al, 2015b; Slembeck & Tyran, 2004; Tubau & Alonso, 2003). However, in none of these studies the repeated experience led to participants consistently switching on all trials.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The typical justification put forward by the subjects is that the likelihood of success if they were to switch curtains is the same as if they were to stay with their original choice of curtain. This mistake is often cited as an example of the equiprobability bias heuristic ( [14], [15], [19], [9]) as described in Lecoutre (1992) [7]. [6].…”
Section: Should Amy Switch?mentioning
confidence: 99%